PENGARUH PERSEPSI ATAS TUJUAN LAPORAN KEUANGAN DAN PENGETAHUAN AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN UMKM (Studi Kasus pada UMKM Di Kota Sungai Penuh Tahun 2020) - Zachari Abdallah; Maryanto . (LPPM - STIE SAKTI ALAM KERINCI, 2020)
ABSTRACT This study aims to examine the perceptions of financial statements and accounting knowledge of the quality of MSME financial statements in the full river city in 2019. The population in this study was MSMEs in the full river city. The sample in this study amounted to 30 respondents with purposive sampling data collection techniques. The data analysis tool used is the Likert scale, multiple linear regression analysis, t test, f test, and test coefficient of determination. Based on the results of the study showed that partially the perception of the purpose of financial statements (X1) on the Quality of Financial Statements (Y) obtained a regression coefficient of 0.324 Testing the relationship between these two variables showed a value of tcount = 2.741 (Ttable> 2.052) with significance = 0.011 (Significant <0 , 05). the magnitude of the influence of Perception on Financial Statements (X1) on the Quality of Financial Statements (Y) of MSMEs in Sungai Kota full of 2019 is 0.16%. the relationship between Accounting Knowledge (X2) to the Quality of Financial reports (Y) obtained a regression coefficient of 0.850 Testing the relationship between the two variables shows the value of tcount = 4.250 (t table> 2.052) with significant = 0.000 (Significant <0.05). the magnitude of the effect of Accounting Knowledge (X2) on the Quality of Financial Statements (Y) is 0.35%. Simultaneously there is a significant effect between Perception of the Purpose of Financial Statements (X1) and Accounting Knowledge (X2) on Consumer Satisfaction (Y). Testing the relationship between variables simultaneously shows the value of fcount = 13,857 (f table> 2.95) with significant = 0,000 (Significant <0.05). The magnitude of the effect simultaneously between perceptions of financial statements (X1) and accounting knowledge (X2) on the quality of financial statements (Y) is equal to 50.7% while the remaining 49.3%.